Political character And Saudi Arabia's fire diplomacy - Malik Kemal (GoAcademica Research & Publishing, 2022)
This paper seeks to trace the political nature behind Saudi Arabia's decision The Kingdom of the Saudis executes Shia cleric Nimr Baqir Al-Nimr using speech act theory. It is no coincidence when the implementation of the NIMR conducted before the implementation of the JCPOA reached Iran with the 5+1 group and the European Union. Saudi political action arises from a political character that is both personal and tribal. This article provides theoretical reinforcement to earlier related research, notably Hermann Frederick Eilts on Saudi Arabian foreign policy, also Philip S. Khoury and Joseph Kostiner highlighting state formation and Arab tribal country patterns. Fire diplomacy tracking model relying on oil (money) and sword (military), a little bit to contribute to the urgency to understand the political nature, including the style of diplomacy, as great maps to analyze the political action of the Arab kingdom of Saud actors in responding to regional and global political dynamics.